2020
DOI: 10.1371/journal.pone.0236524
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on interpersonal aspects of healthcare and patient-centeredness at primary health facilities: A mixed methods study in rural Eastern Uganda

Abstract: Introduction Patient-centered care (PCC) is an approach to involve patients in health care delivery, to contribute to quality of care, and to strengthen health systems responsiveness. This article aims to highlight patient perspectives by showcasing their perceptions of their experience of PCC at primary health facilities in two districts in Uganda. Methods A mixed methods cross-sectional study was conducted in three public and two private primary health care facilities in rural eastern Uganda. In total, 300 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…show their perceptions of their experiences (Waweru et al, 2020). The inclusion of patients in this study would have enriched our views on interpersonal relationships.…”
Section: Discussionmentioning
confidence: 98%
“…show their perceptions of their experiences (Waweru et al, 2020). The inclusion of patients in this study would have enriched our views on interpersonal relationships.…”
Section: Discussionmentioning
confidence: 98%
“…Empathy, communication in multicultural languages, people's involvement in making decisions and designing and implementing solutions effectively empower individualized care for their health [57,59,61]. Empathic support, communication with their doctors, understanding of problems, providers' skills, and management plans were required for improved satisfaction and the effect of interpersonal care [61,62,70]. Communication between service users and providers enhanced high perceived empathy in consultation, trust in relationships, and positive experiences and satisfaction [50,62].…”
Section: Empowerment and Empathymentioning
confidence: 99%
“…A study from the public sector in Uganda found that patients expected PCC, although it was not measured. 9 A South African study in the public sector found significant gaps in the ability of primary care providers to give PCC. 10 Primary care delivery in the Kenyan private sector relies on GPs; 11 however, GPs without postgraduate training may not have been trained in the communication skills that are essential to the practice of PCC.…”
Section: Introductionmentioning
confidence: 99%